Inhibitor of Apoptosis Proteins (IAPs) and Their Antagonists Regulate Spontaneous and Tumor Necrosis Factor (TNF)-induced Proinflammatory Cytokine and Chemokine Production. - LAVELLE, EDWARD; MARTIN, SEAMUS (My University, 2013)
Inhibitor of apoptosis proteins (IAPs) play a major role in determining whether cells undergo apoptosis in response to TNF as well as other stimuli. However, TNF is also highly proinflammatory through its ability to trigger the secretion of multiple inflammatory cytokines and chemokines, which is arguably the most important role of TNF in vivo. Indeed, deregulated production of TNF-induced cytokines is a major driver of inflammation in several autoimmune conditions such as rheumatoid arthritis. Here, we show that IAPs are required for the production of multiple TNF-induced proinflammatory mediators. Ablation or antagonism of IAPs potently suppressed TNF- or RIPK1-induced proinflammatory cytokine and chemokine production. Surprisingly, IAP antagonism also led to spontaneous production of chemokines, particularly RANTES, in vitro and in vivo. Thus, IAPs play a major role in influencing the production of multiple inflammatory mediators, arguing that these proteins are important regulators of inflammation in addition to apoptosis. Furthermore, small molecule IAP antagonists can modulate spontaneous as well as TNF-induced inflammatory responses, which may have implications for use of these agents in therapeutic settings.
PUBLISHED
Keywords: Genetics; Immunology, Inflammation & Infection